Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s11187-005-5603-7
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship and Risk Aversion

Abstract: Evans and Jovanovic (1989, Journal of Political Economy 97(4), 808–827) find that wealth is an important determinant of business startups due to liquidity constraints. However, Cressy (2000, Economic Letters 66, 235–240) argues that if risk aversion is a negative function of wealth, Evans and Jovanovic’s empirical results could be spurious and the positive effect of wealth could be due to the omission of risk aversion in the regression equation. In other words, according to Cressy, one’s wealth does not have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 20 publications
4
58
0
5
Order By: Relevance
“…For instance, Evans and Jovanovic (1989) found that the initial level of assets strongly influences the probability of self-employment (see also Blanchflower and Osvald, 1998;Cabral and Mata, 2003;Hurst and Lusardi, 2004;Kan and Tsai, 2006). Other studies have examined the probability of transition to self-employment after an unexpected financial gain, such as a lottery prize, a windfall gain or a job bonus.…”
Section: From Macroeconomic Outcomes To Microfoundations Of New Firm mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Evans and Jovanovic (1989) found that the initial level of assets strongly influences the probability of self-employment (see also Blanchflower and Osvald, 1998;Cabral and Mata, 2003;Hurst and Lusardi, 2004;Kan and Tsai, 2006). Other studies have examined the probability of transition to self-employment after an unexpected financial gain, such as a lottery prize, a windfall gain or a job bonus.…”
Section: From Macroeconomic Outcomes To Microfoundations Of New Firm mentioning
confidence: 99%
“…Among the personal characteristics of the founder, family background is also singled out as a key factor by econometric estimates which explain new firm formation as an act of self-employment (see Evans and Leighton, 1989;De Wit and Van Winden, 1989;Blanchflower and Oswald, 1998;Hout and Rosen, 2000;Reynolds et al, 2001). For instance, in a very recent paper Burke, FitzRoy and Nolan (1989) found that the initial level of assets strongly influences the probability of self-employment (see also Blanchflower and Osvald, 1998;Cabral and Mata, 2003;Hurst and Lusardi, 2004;Kan and Tsai, 2006). Other studies have examined the probability of transition to self-employment after an unexpected financial gain, such as a lottery prize, a windfall gain or a job bonus.…”
mentioning
confidence: 99%
“…Also, the literature analysis has described that some scholars use the terms of "self-employment" and "entrepreneurship" as synonyms (Akyol, Athreya 2009;Block, Sandner 2009;Bradley, Roberts 2004;Kan, Tsai 2006;Sennikova, Kurovs 2006;Tubergen 2005;Wagner 2006). But according to Krasniqi (2009), self-employment and entrepreneurship are not the same and can't be analyzed as synonymous.…”
Section: From Unemployment To Self-employmentmentioning
confidence: 99%
“…The notion of risk and risk behavior is an important element in the entrepreneurship literature; risk-taking is considered an essential characteristic of entrepreneurs (e.g., Caliendo et al 2009;Douglas and Shepherd, 2002;Forlani and Mullins, 2000;Ibrahim and Ellis, 1993;Kan and Tsai, 2006;Moensted, 2007;Van Gelderen et al, 2000). Brockhaus (1980) defined risk-taking propensity as the perceived probability of receiving the rewards associated with the success of a proposed situation.…”
Section: Literature Review and Research Gapmentioning
confidence: 99%
“…By showing that necessity entrepreneurs have a lower willingness to take risks relative to other entrepreneurs, we contribute to the discussion of the specifics of this particular group (e.g., Bergmann and Sternberg, 2007;Block and Sandner, 2009;Block and Wagner, 2010;Wagner, 2005;Wennekers et al, 2005;Wong et al, 2005). Since risk taking is considered a crucial aspect of entrepreneurial behavior (e.g., Caliendo et al 2009;Douglas and Shep-herd, 2002;Forlani and Mullins, 2000;Ibrahim and Ellis, 1993;Kan and Tsai, 2006;Moensted, 2007;Van Gelderen et al, 2000), we suggest treating them as a separate category in entrepreneurship research and practice.…”
Section: Introductionmentioning
confidence: 96%